Untargeted UHPLC–Q-Exactive-MS-based metabolomics reveals associations between pre- and post-cooked metabolites and the taste quality of geographical indication rice and regular rice - Shi-jie SHI; Gao-yu ZHANG; Cou-gui CAO; Yang JIANG (Journal of Integrative Agriculture, 2023)
Geographical indication (GI) rice refers to the rice of specific geographical origin, which tends to have a good taste quality and a high commodity price. Rice is favored for its soft texture and chewiness after cooking. However, GI rice is also plagued by rice fraud. Understanding the reasons for the excellent taste quality of GI rice and identifying its geographical origin can help maintain the stability of the rice market and promote the development of the rice industry. In this study, we determined the taste quality of rice. Untargeted metabolomics based on UHPLC–Q-Exactive-MS was used to identify metabolites in GI and regular rice before and after cooking. Our findings suggested that GI rice showed lower protein and amylose content, resulting in higher starch gelatinization properties and taste quality. This study identified 520 metabolites, among which 142 and 175 were significantly different between GI and regular rice, before and after cooking, respectively. The increased variety of metabolites after cooking was significantly negatively correlated with the taste quality of rice. GI rice was lower in amino acids and lipid metabolite content before and after cooking, which may be the reason for the excellent taste quality. Through linear discriminant analysis, we found that the differential metabolites of rice after cooking were more accurate in discriminating rice from different geographic origins, up to 100%. This work gained new insights into the metabolites of GI rice, which explains its excellent taste quality. The rice metabolites after cooking could be used for more accurate geographical identification of rice.